2017
DOI: 10.22456/2176-5456.46525
|View full text |Cite
|
Sign up to set email alerts
|

The Retirement Consumption Puzzle: Evidences for Brazil and the State of Rio Grande Do Sul

Abstract: Abstract:The life cycle/permanent income theories predict that consumption would be constant over time but such result has been challenged by some empirical studies which show a systemic decrease in consumption at retirement. This paper aims to investigate the so-called retirement consumption puzzle for Brazil and the State of Rio Grande do Sul. We estimated consumption functions controlling age effects for 12 composite goods using information from the 2008-2009 Household Budget Survey. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, the only study that addressed this question for Brazilian households is Stampe et al (2017), analyzing consumption expenditure across household ages. The authors reported decreases in a few categories of expenditures as the population ages but did not examine the retirement puzzle directly.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the only study that addressed this question for Brazilian households is Stampe et al (2017), analyzing consumption expenditure across household ages. The authors reported decreases in a few categories of expenditures as the population ages but did not examine the retirement puzzle directly.…”
Section: Introductionmentioning
confidence: 99%